A rare case report of prosthetic loosening secondary to diffuse non-pigmented villonodular synovitis after bilateral total knee arthroplasty - Cai, Ke; Yan, Wei; Lin, Leqin; Li, Lei; Yu, Hong; Jiang, Haina; Jiang, Hongjiang (Frontiers in Surgery, 2025)
BackgroundNonpigmented villonodular synovitis (non-PVNS) is a benign yet locally aggressive proliferative disorder affecting the synovium. The occurrence of non-PVNS following knee joint replacement is exceedingly rare.Case presentationThis study investigated synovial mechanisms driving aseptic loosening in bilateral total knee arthroplasty failure over a 14-year period. Radiographic and pathologic analysis tracked sequential failure progression bilaterally. Initial radiographs documented progressive left-knee loosening (2009–2016). Subsequent intraoperative and histologic evaluation (H&E staining) confirmed synovial hyperplasia without PVNS features as the primary mechanism. Post-revision imaging showed immediate left-knee stabilization. However, long-term follow-up revealed sustained left-knee stability (2019) but emergent right-knee loosening (2023), demonstrating interlimb heterogeneity and recurrence risk. Pathologic examination of the revised right knee identified an analogous synovial hyperplasia mechanism (non-PVNS).ConclusionFinal post-revision radiographs validated successful stabilization following both revisions. This longitudinal bilateral case uniquely demonstrates synovial hyperplasia as a replicable driver of aseptic loosening independent of PVNS, highlights heterogeneous progression kinetics and recurrence risk between limbs despite unilateral intervention, and confirms the consistent efficacy of revision arthroplasty for this specific pathology.